Balancing Rationality and Uncertainty: A Contingency Theory Perspective on Organizational Adaptation - Sain, Zohaib Hassan; Eko, Gunawan; Lawal, Uthman Shehu (International Journal of Education, Management, and Technology, 2025)
Organizations operate in increasingly complex environments, requiring adaptive strategies to balance internal rationality with external demands. This study uses Thompson’s (1967) contingency theory to examine how organizations structure themselves in response to environmental uncertainty and technological complexity, integrating insights from resource dependence and institutional theory. Qualitative case studies and quantitative survey data were analyzed using a mixed-methods approach. Technology, healthcare, and manufacturing case studies included semi-structured interviews, document analysis, and observations. A survey of organizational leaders and employees provided quantitative data on structural flexibility, uncertainty, technological complexity, and performance outcomes. Statistical analyses were applied, including regression and structural equation modelling (SEM). Findings reveal that organizations facing high uncertainty adopt flexible structures, while those with complex technologies decentralize decision-making to foster innovation. Institutional pressures also drive organizations to engage in symbolic actions to demonstrate compliance. Integrating qualitative and quantitative data highlighted how technical demands and institutional norms shape adaptation strategies. This study underscores the importance of aligning organizational structure with environmental and technological needs, as contingency theory suggests. However, institutional factors also shape adaptation, making it a multifaceted process. The research contributes to administrative theory by integrating multiple perspectives and offers practical insights for leaders navigating complex environments.